Once upon a car : the fall and resurrection of America's big three automakers - GM, Ford, and Chrysler - Vlasic, Bill. (New York : William Morrow, 2011)
'The Detroit bureau chief for The New York Times takes readers inside the Big Three U.S. automakers for the rise and fall --and rise again? -- of this quintessentially American industry'--
Includes index.
Keywords: Chrysler Corporation; General Motors Corporation; Ford Motor Company; Automobile industry and trade -- United States -- History